PLXND1-mediated calcium dyshomeostasis impairs endocardial endothelial autophagy in atrial fibrillation - Sun, Mengjia; Chen, Zhen; Song, Yuanbin; Zhang, Bo; Yang, Jie; Tan, Hu (Frontiers in Physiology, 2022)
Left atrial appendage (LAA) thrombus detachment resulting in intracranial embolism is a major complication of atrial fibrillation (AF). Endocardial endothelial cell (EEC) injury leads to thrombosis, whereas autophagy protects against EEC dysfunction. However, the role and underlying mechanisms of autophagy in EECs during AF have not been elucidated. In this study, we isolated EECs from AF model mice and observed reduced autophagic flux and intracellular calcium concentrations in EECs from AF mice. In addition, we detected an increased expression of the mechanosensitive protein PLXND1 in the cytomembranes of EECs. PLXND1 served as a scaffold protein to bind with ORAI1 and further decreased ORAI1-mediated calcium influx. The decrease in the calcium influx-mediated phosphorylation of CAMK2 is associated with the inhibition of autophagy, which results in EEC dysfunction in AF. Our study demonstrated that the change in PLXND1 expression contributes to intracellular calcium dyshomeostasis, which inhibits autophagy flux and results in EEC dysfunction in AF. This study provides a potential intervention target for EEC dysfunction to prevent and treat intracardiac thrombosis in AF and its complications.